College Curriculum, Diverging Selectivity, and Enrollment Expansion - Michael Kaganovich; Xuejuan Su (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the impact of expansion of higher education on student outcomes in the context of competition among colleges which differentiate themselves horizontally by setting curricular standards. When public or economic pressures compel less selective colleges to lower their curricular demands, low-ability students benefit at the expense of medium-ability students. This reduces competitive pressure faced by more selective colleges, which therefore adopt more demanding curricula to better serve their most able students. This stylized model of curricular product differentiation in higher education offers an explanation for the diverging selectivity trends of American colleges. It also appears consistent with the U-shaped earnings growth profile we observe among college-educated workers in the U.S.
Keywords: I21; I23; I24; J24; H44; 330; curricular standard; higher education; college selectivity; enrollment expansion; income distribution